2019
DOI: 10.1016/j.jesp.2019.103820
|View full text |Cite
|
Sign up to set email alerts
|

Egocentric foundations of trust

Abstract: Trusting the trustworthy brings benefits whereas trusting the untrustworthy brings harm. Discriminating between the two is key to every social encounter. We propose that humans turn to internal information, namely the self, when judging the trustworthiness of others. Simulating how oneself would behave in situations that involve trust helps to predict how a counterpart may behave. Importantly, using the same self as a basis for judgments about others may result in diverging outcomes, depending on how the infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Conversely, it is also plausible that individuals prone to dishonesty may be more susceptible to conspiracy theories, a tendency attributed to "social projection", where people ascribe their own traits to others (Cho & Knowles, 2013). Experimental evidence has demonstrated that individuals often rely on their own behavior as a reference point to predict the trustworthiness of others (Posten & Mussweiler, 2019). Consistently, past research has shown that people with higher willingness to conspire have higher levels of belief in conspiracy theories (Douglas & Sutton, 2011).…”
Section: Discussionmentioning
confidence: 90%
“…Conversely, it is also plausible that individuals prone to dishonesty may be more susceptible to conspiracy theories, a tendency attributed to "social projection", where people ascribe their own traits to others (Cho & Knowles, 2013). Experimental evidence has demonstrated that individuals often rely on their own behavior as a reference point to predict the trustworthiness of others (Posten & Mussweiler, 2019). Consistently, past research has shown that people with higher willingness to conspire have higher levels of belief in conspiracy theories (Douglas & Sutton, 2011).…”
Section: Discussionmentioning
confidence: 90%
“…The modulation of trust with another individual, known to be closely related to conceptual similarity between self and other (e.g. Fischer, 2009;Posten & Mussweiler, 2019), has been shown to affect the perceived physical similarity between one's self and the other individual. Farmer and colleagues (2014) showed that when participants learned to trust an individual, they perceived their own face to be more similar to the face of that individual.…”
Section: Discussionmentioning
confidence: 99%
“…However, there might be more parsimonious explanations for our findings. First, perceiving a person as trustworthy often means also to perceive the person as similar to oneself (Farmer et al., 2014; Posten & Mussweiler, 2019). Similarity in turn leads to assimilation (Mussweiler, 2003), and thus, potentially, to affirmative answering.…”
Section: Discussionmentioning
confidence: 99%